Elevate Customer Loyalty By Omnichannel Integration Quality: Evidence From The Indonesian Beauty Retail Industry - Galuh Chynintya Rosita (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study uses customer engagement (CE) and relationship program receptiveness (RPR) as mediators in the beauty retail sector to examine the relationship between omnichannel integration quality (OCIQ) and customer loyalty (CL). Data came from 1043 respondents obtained through an online survey and analyzed using PLS-SEM. The five dimensions of OCIQ (channel-service configuration, content consistency, process consistency, assurance quality and channel reciprocity quality) positively influence CE and RPR. Assurance quality has the most significant impact on CE and RPR compared to other OCIQ dimensions. CE significantly mediated CL values more than RPR. This study helps retailers implement omnichannel to understand how to win customers' hearts by providing efficient, trustworthy, convincing service and integrated information. Keywords: Omnichannel Integration Quality, Customer Loyalty, Customer Engagement, Relationship Program Receptiveness, and Retail Marketing